Brachiopods from the Latham Shale Lagerstätte (Cambrian Series 2, Stage 4) and Cadiz Formation (Miaolingian, Wuliuan), California. (January 2022) - Liang, Yue; Holmer, Lars E.; Duan, Xiaolin; Zhang, Zhifei
Abstract: A moderately diverse assemblage of brachiopods from the Latham Shale Lagerstätte (Cambrian Series 2, upper Stage 4) and the upper Cadiz Formation (Miaolingian, Wuliuan), California is described in detail for the first time. The fauna includes both linguliform and rhynchonelliform brachiopods— Hadrotreta primaea (Walcott, 1902 ), Paterina prospectensis (Walcott, 1884 ), Dictyonina pannula (White, 1874 ), and Mickwitzia occidens Walcott, 1908 ; and Nisusia fulleri Mount, 1981 and Wimanella highlandensis (Walcott, 1886 ), respectively—together with olenellid trilobites and hyolithids. The fauna differs from other Cambrian Konservat-Lagerstätten (notably Cambrian Series 2 Chengjiang and Guanshan Lagerstätten, eastern Yunnan) in that the brachiopod shell valves in many cases are still preserved with their original mineralization. Moreover, the excellently preserved shale-hosted valves even include cases with exquisite epithelial cell molds, otherwise only seen in acid-etched material from carbonate rocks. The pitted ornamentation in D. pannula closely resembles that described from Ordovician linguliforms. The unusual preservation of N. fulleri provides important clues for ancestral composition of the brachiopod shell. The two articulated rhynchonelliform species probably represent the oldest records of this group from the west Laurentia. The fauna could also represent the earliest onset of the transition from the Cambrian Evolutionary Fauna (CEF) to the Paleozoic Evolutionary Fauna (PEF).